Fibrosis-4 stage of liver fibrosis predicts cardiovascular outcomes in acute coronary syndrome patients with and without type 2 diabetes mellitus. (January 2023) - Song, Jingjing; Liu, Yupeng; Chen, Jing; Yang, Jie; Wen, Jun; Gao, Jun; Shao, Chunli; Wang, Wenyao; Tang, Yi-Da
Highlights: Liver fibrosis evaluated by the FIB-4 index was associated with adverse outcomes in ACS patients, irrespective of T2DM status. The FIB-4 index is a helpful tool to improve the risk stratification of ACS patients with and without T2DM. Abstract: Aims: We aim to analyze the effect of liver fibrosis, assessed by the Fibrosis-4 (FIB-4) index, on cardiovascular events in acute coronary syndrome (ACS) patients with and without type 2 diabetes mellitus (T2DM). Methods: 6563 ACS patients undergoing PCI were analyzed in this study. Patients were divided into three groups according to literature-based FIB-4 cut-offs: < 1.45, 1.45–3.25, and ≥ 3.25. Results: During the median 2.4-year follow-up, 270 major adverse cardiac and cerebrovascular events (MACCE) and 194 major bleeding were recorded. Intermediate or high FIB-4 scores were significantly associated with an elevated risk of MACCE, mortality, and MI but not associated with ischemic stroke and major bleeding. Further restricted cubic spline analysis showed that FIB-4 as a continuous variable was positively associated with an increased adjusted risk of MACCE. The results were consistent in subgroups with and without T2DM. Conclusions: Liver fibrosis staged by FIB-4 was correlated with an increased risk of MACCE, mortality, and MI in ACS patients who underwent PCI with and without T2DM. FIB-4 index may help risk stratification of ACS patients independent of T2DM status.